Implikasi Penghapusan Masa Tunggu Narapidana sebagai Calon Anggota Legislatif dalam Penerbitan PKPU No 10 Tahun 2023 dan PKPU No 11 Tahun 2023 - Dian Kus Pratiwi; Eka Detik Nurwagita; Mutiara Sabila Hamdani (Fakultas Hukum Universitas Islam Indonesia, 2023)
The KPU has issued two new regulations, namely PKPU Number 10 of 2023 and PKPU Number 11 of 2023. These two regulations were issued as an effort to improve and follow up on the Constitutional Court Decision Number 12/PUU-XXI/2023. After being published, the two PKPUs received a lot of criticism from the public who thought that the KPU had smuggled articles and deviated from the Constitutional Court's decision. This study examines what are the problems with the issuance of PKPU No. 10 of 2023 and PKPU No. 11 Year 2023? And what are the implications of PKPU No. 10 of 2023 and PKPU No. 11 of 2023 in deviations from the Constitutional Court Decision No. 12/PUU-XXI/2023. The method used is normative juridical by examining various laws and regulations, court decisions, and doctrines. The results of this study, the implications of the two provisions for the implementation of law and democracy in Indonesia, namely: 1) the KPU has ignored the principles of forming statutory regulations; 2) KPU tampered with the provisions in the Constitutional Court Decision which seeks to present candidates for legislative members who have clean legal track records; 3) KPU is deemed not to have a vision and mission that is in line with the institutions for preventing and eradicating corruption in Indonesia; and 4) KPU violates the right of the people to get people's representatives with integrity.